2008
DOI: 10.1097/phm.0b013e31816de0f2
|View full text |Cite
|
Sign up to set email alerts
|

Electrodiagnostic Medicine Skills Competency in Physical Medicine and Rehabilitation Residents

Abstract: This project sought to create an educational module including evaluation methodology to instruct physical medicine and rehabilitation (PM&R) residents in electrodiagnostic evaluation of patients with neuromuscular problems, and to verify acquired competencies in those electrodiagnostic skills through objective evaluation methodology. Sixteen residents were trained by board-certified neuromuscular and electrodiagnostic medicine physicians through technical training, lectures, and review of self-assessment exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…The performance component of competency assessment was a point of discussion in the two surveys. The experts agreed on the need for some form of performance assessment, but not a specified 15,28,29 These methods of assessment require live exams and depend on availability of resources. Our suggested approach seemed more flexible and practical from the experts' point of view.…”
Section: Discussionmentioning
confidence: 99%
“…The performance component of competency assessment was a point of discussion in the two surveys. The experts agreed on the need for some form of performance assessment, but not a specified 15,28,29 These methods of assessment require live exams and depend on availability of resources. Our suggested approach seemed more flexible and practical from the experts' point of view.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are only two studies from a single PM&R residency program that have examined educational strategies in either Electrodiagnostic Medicine or Neuromuscular Medicine curriculum for PM&R residents. 5,6 We present here the development of a workshop designed to enhance an existing Electrodiagnostic Medicine curriculum for PM&R residents. The workshop used a combination of teaching strategies to maximize clinically relevant learning.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the Robert Wood Johnson Medical School PM&R residency program published their experiences creating an educational module instructing PM&R residents in electrodiagnostic evaluation and verifying the acquired competencies through objective evaluation methodology. 5,6 This module included a combination of hands-on training, lectures, and review of self-assessment exam concepts, with demonstrated improvement in self-assessment exam scores at initial implementation and at follow up. 5,6 The American Association of Neuromuscular and Electrodiagnostic Medicine (AANEM) has also developed education products including Self -Assessment Examinations, but there are no specific guidelines on how to train residents in Electrodiagnostic Medicine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actualmente existen lineamientos y recomendaciones sobre la formación de los médicos residentes en el área de electrodiagnóstico y sobre la evaluación de las habilidades que se deben adquirir para la ejecución de las diferentes pruebas. En general, se considera que un médico residente debe realizar al menos 200 exámenes de conducción nerviosa dentro de su proceso de formación 2,3 .…”
Section: Introductionunclassified